Application of Long Interval Training Method Based on Low Maximum Aerobic Speed Capacity to Improve Anaerobic Capacity - Santi; Dikdik Zafar Sidik; Ridha Mustaqiem (Journal of Physical Education Health and Sport, 2025)
This study aimed to analyze the effect of long interval training based on low maximum aerobic speed (MAS) on anaerobic capacity. The study employed an experimental method with a one group pretest–posttest design. The participants were 40 undergraduate students of Physical Conditioning Coaching at the Indonesian Education University, aged 18–21 years (mean age 19.33 years), selected using purposive sampling. Anaerobic capacity was measured as a single construct consisting of alactic and lactic anaerobic components, assessed using a 20 m sprint, 4 m × 5 shuttle run, 150 m sprint, and Running-Based Anaerobic Sprint Test (RAST) through the fatigue index. The training intervention consists of long interval training conducted over 16 sessions, with one session per day. The data were analyzed using SPSS version 20 through descriptive statistics and paired sample t-test at a significance level of 0.05. The results showed an increase in the mean anaerobic capacity score from pretest to posttest; however, the paired sample t-test revealed no statistically significant difference between measurements (p > 0.05). These findings indicate that long interval training based on low MAS tended to improve anaerobic capacity, although the effect was not statistically significant. Further studies with larger sample sizes, longer training duration, and controlled experimental designs are recommended to clarify the effectiveness of this training method.